Research on the intervention effect of Five-Element Music combined with Eight-Section Brocade on depression among medical students in higher vocational colleges - Yao, Xiyong; Xiong, Lin; Ouyang, Yiwen; Wang, Hui; Zhu, Lili (Frontiers in Psychology, 2024)
Background: Depression is the main risk factor leading to suicidal ideation among college students. This study focused on observing and assessing how the combination of Five-Element Music and Eight-Section Brocade affected depression levels among medical students attending higher vocational colleges.Methods:From a total of 1030 medical students studying in higher vocational colleges, we selected 160 students who showed depressive symptoms and met the specific criteria for the study. We used the SDS scale to identify these students and made them the participants of our experiment. Participants were randomly divided into four groups: the music intervention group (listening to traditional Chinese Five-Element music for 15 minutes daily), the Eight-Section Brocade intervention group (practicing the Eight-Section Brocade exercises once daily, approximately 15 minutes), the combined intervention group (first practicing the Eight-Section Brocade exercises once, then listening to music for 15 minutes), and the control group (no intervention). Each group consisted of 40 participants.The three intervention groups (excluding the control group) underwent continuous intervention for 4 weeks.The SDS, SAS, and PSQI scales were used for evaluation before and after the intervention.Results: Except for the control group, the SDS, SAS, and PSQI scores of the other three groups were lower after the intervention than before the intervention (P<0.01). After the treatment, the scores on SDS, SAS, and PSQI tests did not vary much between the students who listened to music and those who practiced Eight-Section Brocade (the difference was not statistically significant, P>0.05). However, the students who did both music and Eight-Section Brocade showed significantly lower scores than those who did only one activity (both P<0.01).Conclusion: Five-Element Music and Eight-Section Brocade can improve depression, anxiety, and sleep status among medical students in higher vocational colleges. The combined intervention of the two is more effective than a single method, and it is worth promoting and applying in higher vocational colleges.